48-hour start-up : from idea to launch in 1 weekend - Doherty, Fraser (London : Thorsons, 2016)
Fraser Doherty's '48-Hour-Start-Up' is a handy and essential cheat sheet to starting your own business giving the key steps for developing an idea and getting it to market quickly.
Includes bibliographical references.
Keywords: New business enterprises